Numerical investigation of Pelton bucket geometries for performance improvement - Shah, Hiren; Chaudhari, Gaurangkumar; Dhiman, Vijay; Bhatt, Ravi; Salunkhe, Sachin; Cepova, Lenka (Frontiers in Mechanical Engineering, 2025)
The Pelton turbine is the most effective impulse turbine and has excellent operational performance in high water heads as well as low water rates. The bucket splitter design plays a crucial role, as its design is responsible for its efficiency. The water jet strikes the bucket splitter and produces the forces that move the turbine runner to generate mechanical energy from the kinetic head. A comparative analysis of seven differently designed Pelton turbine buckets is done in this paper. Finite Element Analysis (FEA), as a constructive method to check the static structural analysis in the Pelton turbine bucket, has been used to compare the performance. The effect of changing various parameters like bucket exit angle, bucket width, and bucket thickness on the life of the bucket is discussed here. This study aims to compare and achieve the best design of the Pelton bucket to improve its strength by reducing von mises stress and reducing the deformation. Bucket width is achieved as 110 mm, thickness 5 mm, splitter tip level, and cutout length both at 3 mm, and cutout width at 23.25 mm for effective flow over the bucket surface. The bucket exit angle at the middle section is achieved as 15° to reduce the von mises stress and deformation significantly.